Alfie and the carrot - Haines, Genny (Robert Frederick London, 2003)
*Alfie and the Carrot* is a charming children's story about a young rabbit named Alfie who embarks on an adventurous quest to find the juiciest carrot in the forest. Along the way, he faces challenges, makes new friends, and learns valuable lessons about perseverance and sharing. In the end, Alfie discovers that the best rewards come from kindness and community.